Assessment of Aggregated and Exosome-Associated α-Synuclein in Brain Tissue and Cerebrospinal Fluid Using Specific Immunoassays - Dimitrios Anagnostou (18000752) (2023)
Even though it is currently well-established that α-synuclein aggregation is closely associated with the pathological events in Parkinson’s disease (PD) and several other neurodegenerative disorders, collectively called synucleinopathies, the mechanistic link between α-synuclein aggregates and the onset and progression of neurodegeneration in these diseases remain unclear. The process of aggregation initiates from a structurally distorted monomer that gradually oligomerizes to generate a repertoire of fibrillar and oligomeric multimers that deposit within diseased cells in the brain. Total α-synuclein has been proposed as a potential biomarker in PD, but most of the studies do not discriminate between distinct α-synuclein conformers. To correlate protein measurements to disease pathology, we have developed a conformation-specific ELISA method that selectively detects fibrillar and oligomeric forms of α-synuclein without cross-reacting with monomers. We have used this assay to determine the levels of aggregated α-synuclein in human and mouse brain tissue as well as in CSF and CSF-derived exosomes from patients with synucleinopathy and control subjects. Our results verify the ability of the new assay to detect aggregated α-synuclein in complex matrices and support the idea that the levels of these conformers are related to the age of onset in PD patients, while CSF analysis showed that these species exist in low abundance in CSF and CSF-derived exosomes. Future studies will be required to fully assess the diagnostic usefulness of this ELISA in synucleinopathies. Other Information Published in: Diagnostics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/diagnostics13132192